2007
DOI: 10.1186/1860-5397-3-18
|View full text |Cite
|
Sign up to set email alerts
|

A convenient catalyst system for microwave accelerated cross-coupling of a range of aryl boronic acids with aryl chlorides

Abstract: A convenient microwave accelerated cross-coupling procedure between aryl chlorides with a range of boronic acids has been developed. An explanation for the low reactivity of highly fluorinated boronic acids in Suzuki coupling is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Few other academic research articles have been reported on the hydrolysis of NG (Boschan et al, 1955;Capellos et al, 1984;Tsaplev, 2004), but little information is available on the eventual fate of the nitrate ester. To provide answers to these questions and to gain new insights into the degradation pathway of NG we studied the hydrolysis of the (Walter et al, 1997;Srogi, 2006) and to conduct organic synthesis (Gedye et al, 1991;Clarke et al, 2007). Microwave heating has been successfully used to reduce the time required to extract biopolymers from bacterial cells (Betancourt et al, 2007) and 2,4,6-trinitrotolune from soil from few hours to few min (Kjellstrom et al, 2008), and to treat soil contaminated with chloramphenicol (Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Few other academic research articles have been reported on the hydrolysis of NG (Boschan et al, 1955;Capellos et al, 1984;Tsaplev, 2004), but little information is available on the eventual fate of the nitrate ester. To provide answers to these questions and to gain new insights into the degradation pathway of NG we studied the hydrolysis of the (Walter et al, 1997;Srogi, 2006) and to conduct organic synthesis (Gedye et al, 1991;Clarke et al, 2007). Microwave heating has been successfully used to reduce the time required to extract biopolymers from bacterial cells (Betancourt et al, 2007) and 2,4,6-trinitrotolune from soil from few hours to few min (Kjellstrom et al, 2008), and to treat soil contaminated with chloramphenicol (Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition MW irradiation exhibits selective and volumetric heating properties (which are not features of conventional heating), has different thermodynamic functions to those found for conventional heating, and has excellent controllability [21,22]. Due to the above advantages, MW irradiation has received considerable attention as an effective method for various analytical and chemical applications, such as organic and inorganic synthesis [23][24][25][26], remediation of contaminated soil [14,27,28], macromolecule degradation [29,30], polymerization processes [26,31], extraction in analytical chemistry [32,33], purification of air [34,35], and chemical catalysis [36].…”
Section: Introductionmentioning
confidence: 98%
“…Energy efficiencies have different expressions according to the different objects (pollutant concentrations, COD, TOC, etc.). In this paper, the energy efficiencies associated with pollutant concentrations are calculated using equation(23) and the ones associated with COD or TOC are calculated using equation(24…”
mentioning
confidence: 99%
“…Currently, microwaves are widely used in power transmission, radar, communication, and other fields. In the chemical industry, microwave heating technology has received widespread attention for organic and inorganic synthesis (Clarke et al, 2007;Nuchter et al, 2004;Zhang et al, 2003;Zhang et al, 2007), contaminated soil remediation (Liu and Yu, 2006;Yuan et al, 2006), the polymerization process (Ai et al, 2005;Horikoshi et al, 2003), chemical catalysis (Correa et al, 1998;Nuchter et al, 2004), analytical chemical extraction (Prevot et al, 2001;Srogi, 2006), etc. In addition, with the global environmental protection organizations and governments' attention to green chemistry, the improvement of environmental awareness, and the increasing demand for resource reuse, the microwave has been gradually applied to the recovery and utilization of valuable metals and rare earth elements from low waste resources.…”
Section: Introductionmentioning
confidence: 99%